2018
DOI: 10.1155/2018/7017423
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides in Tobacco Fields: The Integrated Evaluation of Nutritional Intake and Susceptibility on Genomic and Epigenetic Instability

Abstract: Pesticides used at tobacco fields are associated with genomic instability, which is proposed to be sensitive to nutritional intake and may also induce epigenetic changes. We evaluated the effect of dietary intake and genetic susceptibility polymorphisms in MTHFR (rs1801133) and TERT (rs2736100) genes on genomic and epigenetic instability in tobacco farmers. Farmers, when compared to a nonexposed group, showed increased levels of different parameters of DNA damage (micronuclei, nucleoplasmic bridges, and nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 73 publications
0
6
0
1
Order By: Relevance
“…This is different with another research which showed that even though both farmer-owners and farm laborers have the same risk of developing GTS, TBN and Na Oogst tobacco types had more risk towards GTS than Kasturi and Rajang types, because Na Oogst and TBN tobacco leaves are dried in the warehouse, while the Kasturi and Rajang types tobacco types are dried using the sun's heat. The difference in results in this study can be caused by the presence of other variables that influence such as pesticides or another chemical exposure that may have been used by farmer (Kahl et al, 2018). Another factor that might influence is the use of PPE which in this study the majority of respondents have used PPE well even though OHS measures or other safety actions also individual hygiene are poor due to lack of farmers' knowledge (França et al, 2017;Ngajilo, Adams, & Jeebhay, 2018).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is different with another research which showed that even though both farmer-owners and farm laborers have the same risk of developing GTS, TBN and Na Oogst tobacco types had more risk towards GTS than Kasturi and Rajang types, because Na Oogst and TBN tobacco leaves are dried in the warehouse, while the Kasturi and Rajang types tobacco types are dried using the sun's heat. The difference in results in this study can be caused by the presence of other variables that influence such as pesticides or another chemical exposure that may have been used by farmer (Kahl et al, 2018). Another factor that might influence is the use of PPE which in this study the majority of respondents have used PPE well even though OHS measures or other safety actions also individual hygiene are poor due to lack of farmers' knowledge (França et al, 2017;Ngajilo, Adams, & Jeebhay, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…A poor nutritional status makes individuals more vulnerable to disease attacks and can contribute to obesity, which leads to work activity inhibition. Exposure to pesticides in tobacco fields can cause genomic instability, can cause the individual to be more sensitive to nutrient intake, and can lead to epigenetic changes (Kahl et al, 2018). In another study, tobacco-related DNA damage was more significant in individuals who had an inadequate intake of folic acid, vitamin B12, and vitamin B6, as assessed by the Comet test (Fernandes et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent findings have suggested that glyphosate and AMPA affect changes in the human epigenome, associated with alterations in global methylation [ 16 , 17 , 18 , 19 ]. Furthermore our previous studies [ 20 , 21 ] had shown that glyphosate and AMPA significantly altered global DNA methylation in peripheral blood mononuclear cells (PBMCs), methylation in the promoter regions of tumor suppressor genes as well as expression of major cell cycle drivers and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Гораздо меньше публикаций посвящено изучению воздействия средств защиты растений на людей, проживающих в сельскохозяйственных зонах, и лиц, непосредственно занятых в производстве и применении пестицидов. В тоже время в ряде эпидемиологических исследований с применением других методов исследования (метод ДНК-комет, учёт хромосомных аберраций и сестринских хроматидных обменов в лимфоцитах периферической крови и других) получены результаты, свидетельствующие о повышенном уровне нарушений генетических структур в клетках человека в результате воздействия пестицидов [10][11][12][13][14][15].…”
unclassified